ANALISIS KEUNGGULAN KOMPARATIF USAHATANI KOPI DI KABUPATEN BOLAANG MONGONDOW MENGGUNAKAN POLICY ANALYSIS MATRIX (PAM) - Yolanda Pinky Ivanna Rori; Jelly R. D. Lumingkewas; Melissa Lady Gisela Tarore (Sam Ratulangi University, 2019)
The research has been done in Bolaang Mongondow. The aim of the research are to know the comparative advantage of coffee in Bolaang Mongondow North Sulawesi which is analized by Domestic Resource Cost Ratio (DRCR) value and to know the input and output price changes and its impact to the coffee farming comparative advantage. The area of research is selected by purposive method in Bolaang-Mongondow Regencies which are the production centre of coffee. The primarydata are collected through interview with 20 coffee farmers while the secondary data are gained from related institutions. Descriptive analysis using Policy Analysis Matrix (PAM) was implemented in the research to know the comparative advantage value. Sensitivity analysis is used to determine the impact of prices changing to Domestic Resource Cost Ratio (DRCR). The result shows that coffee farming in Bolaang Mongondow has a comparative advantage which is indicated by the value of DRCR 0,0791. Both Private and Social benefit value are profitable. The p rivate benefit is Rp.5.821.590 and social benefit is Rp. 5.525.338.